Trade remedies and the FTAA : a preliminary study - Brown, Kathy-Ann (Caribbean Regional Negotiating Machinery [Bridgetown]BB)
Seeks to raise concerns with respect to the appropriate nature of the response to discriminatory pricing practices. Offers proposals which may be advanced in the context of the FTAA negotiations, having regard to the vulnerabilities of CARICOM Member States. Highlights associated issues involved with the application of countervailing duty measures.